MANAJEMEN LABA DAN KONSEKUENSI EKONOMIS (SUATU PENDEKATAN EKSPERIMEN) - Eni Indriani; Rahmi Sri Ramadhani; Robith Hudaya; Tuti Handayani (Jurnal Aplikasi Akuntansi, 2019)
Earnings management can be seen as a discretion allowed by generally accepted Standards, but it also has a less positive impact if earnings that contain certain objectives of the manager (management) become the basis in economic decision making. However, earnings management does not have to be associated with efforts to manipulate accounting data or information, but tends to be associated with choosing accounting methods to manage earnings that can be done because it is permitted by accounting standards. This study is focused on looking at the two sides of earnings management by using an experimental approach and the economic consequences caused by the chosen perspective. The results of data processing indicate that participants' perceptions of ethical and unethical behavior towards earnings management practices are the same as the economic consequences for the organization.